172k views
3 votes
How do you solve this y= 6x - 3 y= -3 i need to graph so if you can show how to graph it also

2 Answers

4 votes

Answer:

Explanation:

y=6x-3

y=-3

6x-3=-3

6x=-3+3

6x=0,

x=0

y=-3

so solution is point (0,-3)

How do you solve this y= 6x - 3 y= -3 i need to graph so if you can show how to graph-example-1
User Roger Travis
by
5.0k points
6 votes

Answer:

:)

Explanation:

y=6x-3

y=-3

-3=6x-3

-3=6x-3

+3 +3

=6x

User LuvAspNet
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.